PROMOTIF PREVENTIF DIABETES MELITUS MELALUI EDUKASI GAYA HIDUP SEHAT DAN SENAM DIABETES DI DESA NAMBO TAHUN 2025 - B L, Abdurahman Berbudi; Ali, Mohammad; Azizah, Ainun Nur; Farouq, Muhammad; dhiyandari, indhira; fikri, rhama; syauqi, syahdan; yovitaningtyas, taniya (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2025)
Background: The prevalence of diabetes mellitus continues to rise worldwide, including in Indonesia. Cases increased from 200 million in 1990 to 830 million in 2022. Increase public awareness about diabetes mellitus and how to prevent it through healthy lifestyle education and diabetes exercises. This is part of preventive promotive efforts. Diabetes exercise is included in low impact aerobics, the benefits of this exercise can help control blood sugar levels, reduce stress and anxiety, increase stamina, and help maintain weight. Objective: Evaluate and measure the level of knowledge of the community about Diabetes Mellitus disease and healthy lifestyle, as well as blood sugar levels before and after being given education and diabetes gymnastic. Methods: This empowerment uses pre-test and post-test measurements for knowledge levels and blood sugar levels. The sample was people with an age range of 20-80 years. Data analysis involved comparing pre- and post-empowerment scores, using statistical methods to determine program effectiveness. Results: There was an increase in the knowledge of the Nambo Village community related to Diabetes Mellitus and a healthy lifestyle, with a mean pre-test (26.52) and mean post-test (67.39) and a decrease in blood sugar levels with a mean pre (126.17) and mean post (121.07) after being given counseling and diabetic gymnastics.